Analisa Pengaruh Motivasi Konsumen, Persepsi Kualitas, Dan Sikap Konsumen Terhadap Keputusan Pembelian Sepeda Motor PT. Yamaha Indonesia MFG - Ria Wulandari; M. Ifran Sanni; Dani Ramadhan (UNIVERSITAS RAHARJA, 2019)
This research is motivated by a decline in motorcycle sales produced by PT. Yamaha Indonesia MFG in the 2014-2018 period. In this research there was a decrease in the decision on the power of interest in customer purchases on PT. Yamaha Indonesia MFG so that later can be analyzed in the formulation of this paper, that how customer take motorcycle purchase decisions amid the phenomenon of competition and increasingly crowded sales rivalries. The purpose of this research was to analyze the influence of motivation, perceived quality, and customer attitudes toward decisions in purchasing Yamaha motorbikes. This research uses quantitative and qualitative methods. The respondents in this research were 100 people who could meet one to five criteria consisting of; initiator (initiator), influencer (influencer), decision making (decider), purchase (buyer), user (user) motorcycle production PT. Yamaha Indonesia MFG. There are 3 hypotheses formulated and tested using the Regression Analysis method. In qualitative analysis it is obtained from the interpretation of processing data by providing information and explanation. In the results of this research shows the results of Motivation, Quality Perception, and Customer Attitudes have a relationship that has a significant impact on Purchasing Decisions.